The Implementation of School Administrative Management in State Madrasah Tsanawiyah 4 Sragen - Abbas, Ngatmin; Suryanto, Lilis; Fatimah, Meti; Suparman, Fatah (Lembaga Pendidikan Hikmatun Najah Blora, 2023)
This study aims to analyze the implementation of administrative management at MTs Negeri 4 Sragen, with a focus on human resources management, financial management, curriculum management, facilities and infrastructure, as well as extracurricular programs. Document analysis is used to collect data from documents related to administrative management at MTs Negeri 4 Sragen. The research subjects are the headmaster, teachers, and administrative staff involved in the implementation process. The data sources used are documents related to administrative management, such as handbooks, financial reports, and school policies. Data collection techniques include document analysis and interviews. Descriptive analysis is employed to analyze the data. The results show that the implementation of administrative management at MTs Negeri 4 Sragen is carried out in a structured and systematic manner. The quality of human resources, government policies, and organizational culture influence the success of administrative management implementation. Training and socialization, facilities provision, and the use of information technology are efforts made to overcome obstacles in the implementation process. Monitoring and evaluation are conducted periodically to assess the success of administrative management implementation and identify improvements needed in the future. In conclusion, the implementation of administrative management at MTs Negeri 4 Sragen has been successfully carried out well-structured, with efforts to overcome challenges that arise during the implementation process.